Reporting human rights in the Philippines a field guide for journalists and media workers - Batario, Red (Philippine Human Rights Reporting Project, 2009)
Reporting Human Rights in the Philippines: A Field Guide for Journalists and Media Workers is a handy-sized 105-page book designed to help local journalists improve their awareness and coverage of human rights issues. Designed as an introduction to the subject for journalists who know little, it aims to help them incorporate basic human rights issues and thinking into every day reporting.